Pengaruh Kinerja Pegawai Terhadap Kepuasan Kerja Melalui Penempatan Kerja Pada KPN Werdhiyasa - I Gusti Made Dharma Hartawan; Komang Riki Satna Darma (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2022)
This study plans to determine the effect of employee performance on job satisfaction through work placements at KPN Werdhi Yasa. The information checking strategy used in this exploration is Structural Equation Modeling (SEM) by looking at SEM differences, known as visual rendition 3.0 Partial Least Square (PLS). The consequences of this study indicate that employee performance has a positive effect on job satisfaction and sig. where the result is 0.445 with a t-count value of 3.129 > 1.96 with sig. 0.002 <0.050. The impact of employee performance on job placement is positive and sig. where the result is 0.713 with a t-statistic value > 1.96, which is 12.219 and the sig. 0.000 < 0.050. Effect of work placement on job satisfaction with a positive value and sig. where the coefficient is 0.419 and the t-statistic is 2.989 > 1.96, with sig. 0.003 <0.050. The effect of employee performance on job satisfaction with job placement as a mediating variable with a t statistic value of 2.821 > 1.960 and a sig of 0.005 <0.050.